RESPON PETANI PADI TERHADAP PROGRAM ASURANSI PERTANIAN DI KECAMATAN MATAKALI, KABUPATEN POLEWALI MANDAR - M. Saleh S. Ali; Ikawani Ikawani; Eymal Baharsya Demmallino (Jurnal Sosial Ekonomi Pertanian, 2019)
Agricultural insurance is an agreement between the farmer and the insurance company to commit to undertake the risks in farming. This study aims to describe the implementation of agricultural insurance programs, to describe the characteristics of farmers involved in the agricultural insurance program,   to know the response of farmers to the program, and to look for the factors that influence the response of farmers to the program. The study is undertake  in the sub-district (Kecamatan) of Matakali, Polewali Mandar district, West Sulawesi Province. There were 35 farmers involved in the program who werw selected purposefully as respondents of this study. The first and second objective of the study were analyzed descriptively, while the third objective was analyzed using a weighted average calculation with a Likert scale,  and the fourth objective was analyzed by using the chi-square test. The results of the study show that 1) the implementation of the program has been successful but socialization is still lacking and the resolution of applications is difficult, 2) the characteristics of farmers are age, education , income and land area, 3) the cognitive response of consenting farmers, the reaction 4) there is a relationship between age and cognitive response, age with affective response, and education with conative answers